PEMANFAATAN FLIPBOOK SEBAGAI MEDIA EDUKASI ANTI PERUNDUNGAN UNTUK MENGURANGI PERUNDUNGAN ANTAR SISWA DI SEKOLAH DASAR - Ningrum, Fiki Surya; Puspita, Ari Metalin Ika; Purwoko, Budi (Universitas Lampung, 2024)
This study aims to determine the influence of flipbooks as a media for preventing bullying behavior among elementary school students. The data collection technique used is RnD (Research and Development). The results of the study show that (1) bullying can be categorized into three types: physical, verbal, and relational bullying. (2) The causes of bullying are due to negative influences from the home environment, students feeling powerful and feared in the classroom, students feeling envious of other students, and a lack of empathy towards students with special needs. (3) Efforts to prevent bullying include: teachers approaching students involved in bullying, putting up posters prohibiting bullying, collaborating with local police and social services to address bullying incidents, and conducting anti-bullying socialization using flipbooks. This research emphasizes the use of flipbooks as an anti-bullying education medium through document analysis and using the RnD (Research and Development) research type, which focuses on product development and feasibility testing. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh media flipbook terhadap pencegahan perilaku perundungan antar siswa di sekolah dasar. Teknik pengumpulan data yaitu RnD (Research and Development). Hasil penelitian (1) bentuk perundungan dikategorikan menjadi tiga jenis perundungan, yaitu perundungan fisik, verbal, dan relasional. (2) penyebab perundungan karena pengaruh negatif dari lingkungan rumah, siswa merasa berkuasa dan ditakuti di kelas, siswa merasa iri dengan siswa lain, dan kurangnya empati terhadap siswa berkebutuhan khusus. (3) upaya: guru melakukan pendekatan kepada siswa yang terlibat perundungan, memasang poster tentang larangan melakukan tindak perundungan, melakukan kerjasama dengan Babinkamtibmas dan Dinas Sosial untuk mengatasi tindak perundungan yang terjadi, serta melakukan sosialisasi anti perundungan dengan media flibook. Penelitian ini lebih menekankan penggunaan media flipbook sebagai media edukasi anti perundungan dengan teknik studi dokumen dan menggunakan jenis penelitian RnD (Research and Development, dimana jenis penelitian ini fokus pada pengembangan produk serta pengujian kelayakan.